TAHAP PERTAMA PROSES PEMBINAAN NARAPIDANA LAKI-LAKI DI LEMBAGA PERMASYARAKATAN KELAS IIA KUPANG - Samara, Vinsensius; Fernanda Maia, Ledythria; Louisa Henukh Ledoh, Putri Marry; Bendito Mitang, Yohanes; O. Waang, Andre Wiliam (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Correctional Institutions (Lapas) are institutions that have an important role in the development of prisoners, with the main goal of rehabilitating and reintegrating prisoners into society. This article discusses the first stage of the coaching process for male inmates in the Kupang Class IIA Correctional Institution, which focuses on the application of personality development and independence in an effort to reduce the level of recidivism. Coaching at this stage is carried out through a series of programs, including religious awareness education, skills training, discipline coaching, and social activities that support the integration of inmates with the community. This study uses interview and direct observation methods to collect data on the implementation of coaching programs in Kupang Prison. The results of the study show that the coaching stage, which starts from the Maximum Security stage, aims to shape the character of prisoners, increase legal awareness, and prepare them to return to society with positive skills and attitudes. The coaching process at Kupang Class IIA Prison is expected to create better and independent individuals, as well as reduce recidivism rates in the future